2016
DOI: 10.3390/ijms18010020
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Genetics Approaches for the Development of Influenza Vaccines

Abstract: Influenza viruses cause annual seasonal epidemics and occasional pandemics of human respiratory disease. Influenza virus infections represent a serious public health and economic problem, which are most effectively prevented through vaccination. However, influenza viruses undergo continual antigenic variation, which requires either the annual reformulation of seasonal influenza vaccines or the rapid generation of vaccines against potential pandemic virus strains. The segmented nature of influenza virus allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
138
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(141 citation statements)
references
References 197 publications
(332 reference statements)
2
138
0
1
Order By: Relevance
“…In order to generate a pH1N1 LAIV virus, we introduced four ts mutations identified in previous studies into the PB2 (N265S) and PB1 (K391E, D581G, and A661T) ORFs of pH1N1 (Fig. 1A) (7,9,10,39). No mutation was introduced into the viral NP, since pH1N1 NP already contains a G at position 34.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to generate a pH1N1 LAIV virus, we introduced four ts mutations identified in previous studies into the PB2 (N265S) and PB1 (K391E, D581G, and A661T) ORFs of pH1N1 (Fig. 1A) (7,9,10,39). No mutation was introduced into the viral NP, since pH1N1 NP already contains a G at position 34.…”
Section: Resultsmentioning
confidence: 99%
“…First, because a recombinant pH1N1 harboring inhibitory PA-X and NS1 proteins could lead to a more virulent virus (35)(36)(37)(38), we selected, for safety reasons, to use the ca, ts, and att pH1N1 LAIV virus. Second, we and others have previously shown that LAIVs provide a more sensitive approach to study mutations affecting overall viral replication and pathogenicity (5,7,(9)(10)(11)39). Finally, the results obtained from our studies could be used to identify and develop more efficient LAIV candidates with acceptable safety profiles by modulating the virus' ability to control the host immune responses (7,11).…”
mentioning
confidence: 94%
“…The current challenge is to develop strategies that allow strong antibody responses to the HA stem region, the less immunogenic region of the HA molecule. Several approaches have already been tested including the use of headless HA molecules, HA molecules with hyperglycosylated heads, or sequential immunization with chimeric HA molecules [28,29]. Both humoral and cellmediated arms of the immune system should be activated to confer broadly protective immunity.…”
Section: The Future Of Influenza Vaccination: Toward a Universal Vaccinementioning
confidence: 99%
“…In 1981, Racaniello and Baltimore provided the basis of this approach with poliovirus 19 . Since then, numerous reverse genetics systems have been developed for positive-and negative-stranded RNA viruses 4,18,[20][21][22][23][24] . Plasmid-based reverse genetic approaches allow the rescue of infectious recombinant viruses by the transfection of one or more plasmids encoding the components necessary for the de novo generation of infectious virus particles into cultured cells.…”
mentioning
confidence: 99%
“…Importantly, reverse genetic techniques are powerful platforms to modify the viral genome and they have provided critical insights into replication and pathogenesis of multiple viruses 18 . Importantly, viral reverse genetic approaches have also been used as platforms to develop novel and more effective live-attenuated vaccines (LAVs) against viral infections and have significantly contributed to the development of antiviral treatments 18,20 . However, there are intrinsic limitations in the in vitro recovery of recombinant viruses using reverse genetic approaches, mostly associated with cell culture-adaptive mutations that might restrict and/or change the phenotype of the virus in vivo 25,26 .…”
mentioning
confidence: 99%